Penyidikan terhadap Anak Penyalahguna Narkotika Menurut Undang-Undang Sistem Peradilan Pidana Anak di POLRES Simalungun - Nabila Siregar; Zaid Alfauza Marpaung (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The development of the times has brought convenience to human life, but it has also brought bad effects, one of which is Narcotics. Narcotics are not only easily available to adults but have reached minors. Narcotics abuse is a crime and the perpetrators must be legally processed, for underage perpetrators the legal process is guided by Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. The Juvenile Criminal Justice System regulates the entire process of resolving cases of children in conflict with the law starting from the investigation stage to the accompaniment stage after serving a sentence. So that with legal establishment, children who are in conflict with the law can be protected and guaranteed their rights, one of which is during the initial examination process at the police, namely investigation. Investigation provisions are regulated in the second part of Articles 26 to 29 of Juvenile Criminal Justice System . However, in its implementation, investigators encountered many obstacles in carrying out the SPPA Law. This research entitled Investigation of Drug Abusing Children According to the Criminal Justice System Law aims to find out how the Juvenile Criminal Justice System is implemented in the process of investigating children who abuse narcotics at the Simalungun Police Resort. Keywoords: children, investigation, drug abusing, SPPA Law